NSAID Treatment Before and on the Early Onset of Acute Kidney Injury Had an Opposite Effect on the Outcome of Patients With AKI - Wang, Hai; Liu, Tong; Li, Qinglin; Cui, Ruixia; Fan, Xueying; Tong, Yingmu; Ma, Shuzhen; Liu, Chang; Zhang, Jingyao (Frontiers in Pharmacology, 2022)
Background: NSAIDs is one of the most frequently used medications and a risk factor for AKI. However, the optimal time of NSAIDs in patients with AKI is unknown. Methods: A secondary analysis of a multicenter, randomized clinical trial including adult inpatient with acute kidney injury.Univariate analysis, multivariate analysis, and subgroup analysis were used to explore the impact of NSAIDs during the early onset of AKI on the outcome of patients with AKI. Results: 6030 patients with AKI were enrolled in the study. Following were the findings of the multi-factor analysis: NSAIDs treatment within 72 h and 24 h before the onset of AKI were not associated with AKI progression, dialysis, or discharge from dialysis; only NSAIDs treatment within 24 h onset of AKI was associated with these outcomes, and the ORs value of them were independently 1.50 (95% CI: 1.02 to 2.19, P = 0.037), 4.20 (95% CI: 1.47 to 11.97, P = 0.007) and 0.71 (95% CI: 0.54 to 0.92, P = 0.011); only NSAIDs treatment within 24 h onset of AKI would decrease the 14-day mortality, the OR value was 0.52 (95% CI: 0.33 to 0.82, P = 0.005). Subgroup analysis revealed that when patients with age ≥ 65 years, CKD (chronic kidney disease), congestive heart failure, hypertension, and liver disease, NSAIDs treatments within 24 h onset of AKI would deteriorate the outcome of patients with AKI. Conclusion: Before an early onset of AKI, NSAIDs treatment might be safe, but during the onset of AKI, even early NSAIDs treatment would deteriorate the outcome of patients with AKI.